Non-Standard Employment Relationships in the Digital Era: A Normative Study on the Regulatory Void in Protecting Ride-Hailing Drivers - Fransisco, Fransisco; Nugroho, Any; Natania, Elsa Beatris Rut (CV. Social Politic Genius (SIGn), 2025)
Amid the massive expansion of the digital economy, millions of ride-hailing drivers in Indonesia work under conditions of legal vulnerability due to the use of a ‘partnership’ scheme that systematically conceals a genuine employment relationship. This phenomenon has created a fundamental regulatory void, wherein the national labor law framework fails to provide adequate protection. This research aims, first, to critically analyze the legal character of the relationship between drivers and platforms, and second, to examine the incompatibility of this partnership model with the principles of Indonesian industrial relations. Through a normative legal research method using statutory, conceptual, and comparative approaches, it was found that the ‘partnership’ label is proven to be a legal fiction. Substantively, the three elements of an employment relationship (work, wages, and orders) as stipulated in Law Number 13 of 2003 have been fulfilled. The element of ‘orders’ is strongly manifested through the mechanism of digital subordination or algorithmic management. This denial of legal status directly erodes the foundations of worker protection, nullifying access to social security, fair dispute resolution mechanisms, and the right to associate. Therefore, this research asserts that the relationship is a disguised employment relationship that demands decisive state intervention. A fundamental legislative reform of Law Number 13 of 2003 is necessary to respond to the dynamics of digital work in a fair and socially just manner.